72 Distinguishing features of MIS-C to other paediatric febrile diseases in the acute setting. (7th October 2022) - Butters, Claire; Spracklen, Timothy; Stander, Raphaella; Day, Jonathan; Facey-Thomas, Heidi; Zuhlke, Liesl; Scott, Christiaan; Webb, Kate
Abstract: Background: Multisystem inflammatory syndrome in children (MIS-C) presents with fever, shock, rash, abdominal pain and raised inflammatory markers, as well as common features of inflammatory childhood illnesses. In the acute setting, especially in countries where infectious diseases are common differential diagnoses, it is challenging to diagnose MIS-C. Therefore, data differentiating MIS-C from other inflammatory and/or febrile diseases at presentation is needed. Methods: Prospective data was collected from children admitted to the Red Cross War Memorial Children's Hospital in Cape Town, South Africa from May 2020 to end November 2021 where MIS-C was part of their differential diagnoses. Clinical features on the day of admission were compared between children with confirmed MIS-C (MIS-C+) and those with alternate diagnoses (MIS-C-). Results: In this time period, 60 children were MIS-C+ and 34 were MIS-C-. There was no significant difference in age ( p = 0.321), sex ( p = 0.525), ethnicity ( p = 0.279), or in the frequency of comorbidities ( p = 0.151) between the two groups. The presence of conjunctivitis (OR = 8.12), rash (OR = 8.67), tachycardia (OR = 2.8) and oral mucositis (OR = 3.75) was associated with MIS-C+ while abdominal pain and hypotension were not. MIS-C+ had statistically higher median C-reactive protein (CRP), pro-brain natriuretic protein (pro-BNP) and ferritin, and lower median lymphocyte count, platelet count and sodium levels than MIS-C-. Ferritin discriminated MIS-C+ well (AUC = 0.86) with a 94% sensitivity and 60% specificity at a cut off of > 195ng/l. Sodium had an AUC of 0.72, with a 70% sensitivity and 71% specificity at a cut off of < 132.5 mmol/l. CRP did not distinguish MIS-C well (AUC = 0.52) and although they had good AUC, platelet count and pro-BNP had cut off values in the normal range decreasing clinical utility. Conclusion: We provide evidence for the use of accessible clinical and laboratory variables for the diagnosis of MIS-C in diverse settings. Implications: These data will aid clinicians to do a rapid diagnosis (and ultimately treat earlier) of patients with MIS-C in the acute setting, especially those in under-resourced settings.